2000
DOI: 10.1111/j.1745-459x.2000.tb00276.x
|View full text |Cite
|
Sign up to set email alerts
|

Children's Perceptions of and Preferences for Vegetables in the West of Scotland: The Role of Demographic Factors

Abstract: Forty year old children participated in this study to measure their perceptions of common vegetables. North Glasgow was selected as the locale because it contains the areas with Scotland's lowest and highest fruit and vegetable intakes. The impact of socioeconomic status upon the children's perceptions and preferences was examined, as were age, gender and frequency of vegetable consumption. The repenory grid method was used to elicit the perceptual data. Personal attributes were scored on a 10-cm linear scale,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 26 publications
1
13
0
1
Order By: Relevance
“…This study found that it was the unfamiliarity or typicality of the colour that raised expectations rather than specific colours. The findings are in accordance with the notion that colour/flavour associations play a role in shaping expectations (Baxter et al, 2000). It may be that unfavourable associations have been established in children for typically coloured vegetables and that such associations are not present for the atypically coloured vegetables, which were novel to most children.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This study found that it was the unfamiliarity or typicality of the colour that raised expectations rather than specific colours. The findings are in accordance with the notion that colour/flavour associations play a role in shaping expectations (Baxter et al, 2000). It may be that unfavourable associations have been established in children for typically coloured vegetables and that such associations are not present for the atypically coloured vegetables, which were novel to most children.…”
Section: Discussionsupporting
confidence: 90%
“…Colour was suggested to affect children's acceptance for vegetables (Baranowski et al, 1993;Baxter et al, 2000;Zeinstra et al, 2007Zeinstra et al, , 2010 and the present findings enhance our understanding of the role of colour. Baxter et al (2000) found brightly coloured vegetables to be preferred to dark green vegetables. This study found that it was the unfamiliarity or typicality of the colour that raised expectations rather than specific colours.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…It is known that preferences formed in childhood normally continue into adulthood, and that children are more receptive to changes in food habits than adults (Baxter et al, 2000). Thus the Brazilian National School Meals program (PNAE), whose objectives are to contribute to biopsychosocial growth and development, learning, school performance and the formation of healthy food habits by way of the offer of adequate school meals (Brasil, 2015), appears as an important strategy for insertion of the fish consumption habit in any region characterized by low consumption of this food.…”
Section: Introductionmentioning
confidence: 99%